Model-Model Evaluasi Pendidikan Dasar (Scriven Model, Tyler Model, dan Goal Free Evaluation) - Helda Kusuma Wardani; Fajarsih Darusuprapti; Mami Hajaroh (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2022)
Microsoft Office Translator Program evaluation becomes important for educators to understand and do, because every educator must be able to become an evaluator. Program evaluation models are wide variety and their function depends on the type of program evaluated. In education there are at least three types of programs, namely processing programs, services, and general. Evaluation of suitable processing programs is evaluated with the Formative-Summative Evaluation Model or Scriven Model, GOE or Tyler Model, and GFE Model. Two program evaluation models namely Scriven model and Tyler model are used in Indonesia. Both of these models are often used by teachers when designing, implementing, and evaluating their learning programs.